Policy support and firm performance during the COVID-19 pandemic: Evidence from Colombia - Arturo José Galindo Andrade; Jorge Andrés Tovar Mora (Inter-American Development Bank (IDB), 2022)
The pandemic hit the Colombian economy as hard as other countries. Using a novel Business Pulse Survey, this paper tests the effect of government support and COVID-19 cases on firms' performance. A one-standard-deviation increase in government support (in periods in which the pandemic's intensity was average) increased the percentage of firms reporting normal operations by 4.8 percent. Political demonstrations in spring 2021, however, reduced the percentage by 13 percent each month they lasted. Firms' financial distress also counters the impact of government support, suggesting the need to ease firms' access to financial markets. Last, we show that investing in digital solutions improved firms' performance but remote work degraded it.
Keywords: D22; L20; L25; O10; 330; COVID-19; Firm performance; Policies; Working from home